2004
DOI: 10.1080/02713680490503787
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical investigation of the efficacy of an artificial tear solution containing hydroxypropyl-guar as a gelling agent

Abstract: The tear product containing HP-guar, PEG 400 and propylene glycol satisfies several pre-clinical criteria for an appropriate artificial tear formulation. It gives long-term desiccation protection of the intact cornea and also epithelial cells in culture and has no apparent deleterious affects on cells. It also provides conditions in which a damaged corneal epithelium can recover normal barrier function. The combination of ingredients in the formulation appears to provide an effective mucomimetic artificial tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 15 publications
3
52
0
3
Order By: Relevance
“…31 The increase in TBUT and the improvement of the OSDI and its subscales after treatment with HP-Guar may be due to its peculiar mechanism of action. Upon binding Systane content, stored at a pH of 7.0, with tears, which have a pH between 7.5 and 7.8, borate ions meet with the HP-Guar and form a matrix, which increases the retention of compound's lubricant (PEG 400 and PG), resulting in an increase in the stability of the tear film on the ocular surface, and thus in decreased corneal desiccation 32 and permeability. 15 In both groups of patients, a significant reduction of the CD11b marker was found.…”
Section: Discussionmentioning
confidence: 99%
“…31 The increase in TBUT and the improvement of the OSDI and its subscales after treatment with HP-Guar may be due to its peculiar mechanism of action. Upon binding Systane content, stored at a pH of 7.0, with tears, which have a pH between 7.5 and 7.8, borate ions meet with the HP-Guar and form a matrix, which increases the retention of compound's lubricant (PEG 400 and PG), resulting in an increase in the stability of the tear film on the ocular surface, and thus in decreased corneal desiccation 32 and permeability. 15 In both groups of patients, a significant reduction of the CD11b marker was found.…”
Section: Discussionmentioning
confidence: 99%
“…The tear product containing HPG, PEG and PG provides conditions in which a damaged corneal epithelium can recover normal barrier function. It also provides an effective mucomimetic artificial tear product [35]. Systane, the first eye drop to incorporate HPG, designed to develop into a soft gel when placed on the eye allows cell repair in an ocular surface microenvironment [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Once instilled in the eye, where the pH is around 7.5, this link is dissociated, and HPG binds to borate and forms a gel with bio adhesive properties, increasing the duration of exposure to the active ingredients (UBELS et al, 2004;DAVITT et al, 2010;SPRINGS, 2010). HPG molecules bind to the hydrophobic regions, i.e., areas where the glycocalyx integrity is compromised, and promoted local healing and lubrication (UBELS et al, 2004). HPG solutions are an effective treatment for KCS as they increase the tear break up time (TBUT) (OUSLER et al, 2007).…”
Section: Lubricant Agentsmentioning
confidence: 99%
“…HPG solutions are an effective treatment for KCS as they increase the tear break up time (TBUT) (OUSLER et al, 2007). A commercial solution of HPG (Systane Ultra ® ) has been shown to provide protection against desiccation in vivo (rabbit models) and in vitro, and provided a favorable environment for the regeneration of epithelial cells (UBELS et al, 2004 (OUSLER et al, 2007;COHEN et al, 2014). However, some studies reported that there is no difference between the formulations Systane ® , Optive ® and Refresh LiquiGel ® regarding the reduction of symptoms, consumer satisfaction, and safety of the product (DAVITT et al, 2010;COHEN et al, 2014).…”
Section: Lubricant Agentsmentioning
confidence: 99%
See 1 more Smart Citation